Customer Base Strategies (International Journal of Scientific Research and Management (IJSRM), 2018)
Growing and sustaining the customer base of an organization is always a challenge to firms’ operating in an intense and competitive industry and where the cost of brand switching is relatively low. For an organization to adopt any strategy, the need to scan its environment will be necessary to avoid making a strategic mistakes that are capable of causing an organization its life as a corporate entity. The study aimed at identifying and discussing strategies an organization can adopt in growing and sustaining its market share in a given industry. These strategies include; innovation strategy, market segmentation strategy, market expansion strategy, 80/20 business strategy, and customer relationship retention strategies. A research model was formulated for the purpose of guiding further studies.